A Review of Auditor Gender and Accountability Pressure’s Impact on Audit Risk Judgments - Marie Solange Lopes (Business Ethics and Leadership)
As audit judgments significantly influence the quality of audits and financial information, it is important to consider the factors affecting them and how they interact. Unfortunately, such factors as gender and accountability pressure and their impact on audit judgments have been historically under-researched. Prior studies show that due to gender differences, female auditors relate to more conservative audit judgments and better audit quality. These gender differences revolve around behavior, socialization, decision-making, information processing, reporting relationships, and career attitudes. However, they are moderated by experience, knowledge, prior commitment, and audit effort related to audit risk. Accountability pressure has also been shown to impact audit judgments based on the type and level of pressure and could be moderated by gender. Yet, existing literature fails to connect gender and accountability pressure to study their combined impact on audit judgments. This literature review seeks to demonstrate that gender combined with accountability pressure results in more conservative audit judgments and, hence, better audit quality. This analysis concludes that since both gender and accountability pressure impact audit judgments, and gender is an individual characteristic with a moderating effect on accountability pressure, the combination of gender and accountability pressure thus positively affects audit judgments. This analysis has implications for practice on factors affecting auditor judgment and extends the academic literature by applying accountability pressure, gender as well as selectivity, and social intuitionist theories to auditor judgment.